Penerapan Dupak Online bagi pustakawan di Kementerian Pertanian - Eka Kusmayadi (Perpustakaan IPB, 2020)
The achievements of librarians' work are shown by their success in carrying out every item of activities as stated in Permenpan no. 9 of 2014 and the regulation of the Head of the National Library No. 11 of 2015. To get credit numbers, each librarian must make a list of proposals for credit number submission (DUPAK). During this time, dupak proposals made by librarians vary greatly. There are librarians who quickly collect dupak, there are librarians who have difficulty making DUPAK so that it takes a long time for many years, some are at all up to the end of dupak's proposed tolerance, which is five years still can’t make dupak even end up with dismissal as a functional official librarian. This paper aims to provide an explanation of the use of online DUPAK applications for librarians in compiling DUPAK. To improve the ease and speed of the process of preparing and collecting DUPAK librarians, DUPAK online can help librarians in the Ministry of Agriculture. For the TPJP secretariat the application can accelerate the delivery of DUPAK from librarians and the provision of librarian staffing administration needs. But to achieve this, the assessment team needs to improve its competence in computerized operations. Librarians must be disciplined in compiling DUPAK in the way every completed work is immediately presented into the system, and more socialization is needed for librarians, assessment teams and members of the TPJP secretariat before dupak online application is applied to all librarians.